2003
DOI: 10.1046/j.1468-1331.2003.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

EFNS Guidelines on cognitive rehabilitation: report of an EFNS Task Force

Abstract: In 1999, a Task Force was set up under the auspices of the European Federation of Neurological Societies with the aim to evaluate the existing evidence for the clinical effectiveness of cognitive rehabilitation. This review led to the development of a set of guidelines to be used in the management of adult patients with cognitive disorders due to acquired focal neurological damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
98
0
8

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 138 publications
(185 reference statements)
4
98
0
8
Order By: Relevance
“…We focused on a specific set of potential moderator variables suggested by the Cicerone et al (2000Cicerone et al ( , 2005 and Cappa et al (2003Cappa et al ( , 2005 reviews, as well as by our reading of the literature. Table 1 presents the distribution of studies across levels of several qualitative candidate moderator variables, as well as descriptive statistics for quantitative candidate moderator variables.…”
Section: Moderatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…We focused on a specific set of potential moderator variables suggested by the Cicerone et al (2000Cicerone et al ( , 2005 and Cappa et al (2003Cappa et al ( , 2005 reviews, as well as by our reading of the literature. Table 1 presents the distribution of studies across levels of several qualitative candidate moderator variables, as well as descriptive statistics for quantitative candidate moderator variables.…”
Section: Moderatorsmentioning
confidence: 99%
“…In this approach, evidence from stronger research designs, referred to as Class I studies, has greater influence on the final recommendations of the reviewer(s). The European Federation of Neurological Societies Task Force on Cognitive Rehabilitation was created in 1999 to evaluate the existing evidence for the clinical effectiveness of, and treatment guidelines for, cognitive rehabilitation in stroke and TBI (Cappa et al, 2003). This systematic review and a subsequent update (Cappa et al, 2005) found limited high-quality evidence (i.e., Class I) supporting some forms of cognitive rehabilitation; specifically, treatments for visual neglect and apraxia after stroke, impairments of attention after TBI, and memory dysfunction after either TBI or stroke.…”
mentioning
confidence: 99%
See 3 more Smart Citations